New insights into phase distribution, phase composition and disorder in Y2(Zr, Sn)2O7 ceramics from NMR spectroscopy1. Issue 14 (14th April 2015) - Ashbrook, Sharon E.; Mitchell, Martin R.; Sneddon, Scott; Moran, Robert F.; de los Reyes, Massey; Lumpkin, Gregory R.; Whittle, Karl R.
<x xml:space="preserve">Abstract</x> The use of solid-state NMR spectroscopy to provide new insight into the composition and atomic-scale disorder in pyrochlore-based ceramics produces a very different picture to that obtained using other techniques.